A potential therapeutic role for angiotensin-converting enzyme 2 in human pulmonary arterial hypertension. Issue 6 (21st June 2018) - Hemnes, Anna R.; Rathinasabapathy, Anandharajan; Austin, Eric A.; Brittain, Evan L.; Carrier, Erica J.; Chen, Xinping; Fessel, Joshua P.; Fike, Candice D.; Fong, Peter; Fortune, Niki; Gerszten, Robert E.; Johnson, Jennifer A.; et al.
Pulmonary arterial hypertension (PAH) is a deadly disease with no cure. Alternate conversion of angiotensin II (AngII) to angiotensin-(1–7) (Ang-(1–7)) by angiotensin-converting enzyme 2 (ACE2) resulting in Mas receptor (Mas1) activation improves rodent models of PAH. Effects of recombinant human (rh) ACE2 in human PAH are unknown. Our objective was to determine the effects of rhACE2 in PAH. We defined the molecular effects of Mas1 activation using porcine pulmonary arteries, measured AngII/Ang-(1–7) levels in human PAH and conducted a phase IIa, open-label pilot study of a single infusion of rhACE2 (GSK2586881, 0.2 or 0.4 mg·kg −1 intravenously). Superoxide dismutase 2 (SOD2) and inflammatory gene expression were identified as markers of Mas1 activation. After confirming reduced plasma ACE2 activity in human PAH, five patients were enrolled in the trial. GSK2586881 was well tolerated with significant improvement in cardiac output and pulmonary vascular resistance. GSK2586881 infusion was associated with reduced plasma markers of inflammation within 2–4 h and increased SOD2 plasma protein at 2 weeks. PAH is characterised by reduced ACE2 activity. Augmentation of ACE2 in a pilot study was well tolerated, associated with improved pulmonary haemodynamics and reduced markers of oxidant and inflammatory mediators. Targeting this pathway may be beneficial in human PAH. The ACE2–Ang-(1–7)–Mas1 axis is probably involved in the pathophysiology of human pulmonary arterial hypertension http://ow.ly/pgS530jOxnd